Large-scale scientific computing : 10th international conference, LSSC 2015, Sozopol, Bulgaria, June 8-12, 2015, revised selected papers /: 10th international conference, LSSC 2015, Sozopol, Bulgaria, June 8-12, 2015, revised selected papers. (2015) - Unknown
No abstract available